Altering frontiers : organizational innovations in healthcare - Grenier, Corinne; Oiry, Ewan, 1973- (London, UK : ISTE, Ltd. ; Hoboken : Wiley, 2021)
How can healthcare systems be transformed by reimagining their multiple silos to favor processes and practices that are more responsive to local, horizontal initiatives? Altering Frontiers analyzes numerous experiences, using a multidisciplinary approach, paying attention to certain actors, collectives and organizational arrangements.
Innovations as Seen by Stakeholders. Innovations as Seen by Stakeholders -- Recognition of Patients' Experiential Knowledge and Co-production of Care Knowledge with Patients and Citizens in the 21st Century / Luigi Flora -- Innovative Organizations and Professional Strategies: The Nursing Professional Space / Philippe Moss -- Managed Communities of Practice in the Gerontology Sector: Case of a CoP of Gerontology Volunteers in Sweden / Bertrand Pauget -- Innovations on the Collective Side. Innovations on the Collective Side -- Moving from Partitioning to Transversality in Operating Rooms using Robot-assisted Surgery / Delphine Wannenmacher -- Clinical Poles of Activity, an Opportunity for New Cooperation Between the Actors? The Case of a Hospital / Christelle Havard -- Learning from Reforms Aiming to Disseminate Innovative Organizational Models: The Case of Family Medicine Groups in Quebec / Frederic Gilbert -- Variety and Performance of Innovative Organizational Structures: The Emergence of Territorial Support Platforms / Matthieu Sibu, Sandrine Cueille, Tamara Roberts -- Reflective Insights on Organizational Innovations in Healthcare. Reflective Insights on Organizational Innovations in Healthcare -- Proposals for New Approaches to Contributory Evaluation of Healthcare Pathways from Interface Organizations / Jessica Gheller, Christian Bourret, Gerard Mick -- Innovation and Absorptive Capacity of Organizations in the Healthcare Field / Corinne Grenier, Christine Dutrieux -- Quality Management in Hospitals: The Two Faces of Rationalization Through Indicators / Hugo Bertillot -- List of Authors -- Index -- Other titles from iSTE in Innovation, Entrepreneurship and Management
Includes index.
John Wiley and Sons
Keywords: Medical innovations; x; Medical innovations